Microsurgical varicocelectomy - Beharka, Rastislav; Pacík, Dalibor; Khamzin, Azat; Nussir, Mohamed Ismail Abdo (Abstracts of the 3rd Czech and International Congress of Andrology, 2008)
Varicocelectomy is the most common procedure for male infertility. The introduction of microsurgical techniques has revolutionized the treatment of male infertility. Material and methods: Over a 4-year period, 217 patients underwent microsurgical varicocelectomy at our center. Pre-operative semen values were compared with the post-operative values. Results: Significant improvement of spermiogram occurs in 70.35%. Pregnancy rate 41%. Conclusions: Microsurgical varicocelectomy is a safe and effective option for the management of varicocele-induced male infertility. It leads to improvement in all semen parameters and increases the possibility of spontaneous pregnancies.